Perceptions of artificial intelligence in healthcare curricula: insights from a nationwide survey of medical students - Almusharraf, Ahlam; Shaikh, Abdul Khalique; Attar, Razaz Waheeb; Alwassil, Osama (Frontiers in Education, 2025)
IntroductionIn an era where artificial intelligence (AI) is rapidly transforming the healthcare sector, understanding the perceptions of future healthcare professionals is vital. This study aims to assess the attitudes of healthcare students in Saudi Arabia toward AI and to evaluate their views on its impact on medical education and future healthcare careers.MethodsA nationwide survey was conducted across 21 universities in Saudi Arabia. The study targeted healthcare students from various academic years and disciplines. Data were collected on students' exposure to AI, their educational backgrounds, and their perceptions of AI's role in healthcare.ResultsThe survey revealed significant gender-based differences in perceptions of AI. There was a strong consensus on the importance of integrating AI into healthcare curricula. However, respondents also expressed caution regarding the application of AI in clinical practice. Attitudes varied based on students' year of study, level of AI exposure, and educational background, indicating a complex set of influences on their views.DiscussionThe findings highlight the multifaceted perspectives of future healthcare professionals regarding AI. The results suggest the necessity of developing tailored educational strategies that incorporate AI into the curriculum while addressing concerns about its clinical implementation. These insights are essential for preparing students for an AI-integrated healthcare system in the Kingdom of Saudi Arabia.